2016
DOI: 10.1039/c5fo00705d
|View full text |Cite
|
Sign up to set email alerts
|

Effects of post-suckling n-3 polyunsaturated fatty acids: prevention of dyslipidemia and liver steatosis induced in rats by a sucrose-rich diet during pre- and post-natal life

Abstract: The interaction between fetal programming and the post-natal environment suggests that the post-natal diet could amplify or attenuate programmed outcomes. We investigated whether dietary n-3 long-chain polyunsaturated fatty acids (n-3 PUFAs) at weaning resulted in an amelioration of dyslipidemia, adiposity and liver steatosis that was induced by a sucrose-rich diet (SRD; where the fat source is corn oil) from the onset of pregnancy up to adulthood. During pregnancy and lactation, dams were fed an SRD or the st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 49 publications
0
7
0
1
Order By: Relevance
“…While these parameters were not measured in the current study, Chicco et al . () reported that maternal consumption of a high‐sucrose diet was associated with increased saturated fat content of the milk. The increased fat mass observed in 3‐week‐old offspring appeared to be mainly driven by deposition in the omental depot.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…While these parameters were not measured in the current study, Chicco et al . () reported that maternal consumption of a high‐sucrose diet was associated with increased saturated fat content of the milk. The increased fat mass observed in 3‐week‐old offspring appeared to be mainly driven by deposition in the omental depot.…”
Section: Discussionmentioning
confidence: 99%
“…There may have also been a difference in the concentrations of specific milk lipids, as previously reported by Chicco et al . () for dams fed a high‐sucrose diet during lactation, or differences in other milk components. This needs to be investigated in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…In a rat model of glucocorticoid-induced programming, postnatal administration of omega-3 PUFAs mitigated programmed hypertension and hyperlipidemia in male offspring 124 and adipose tissue inflammation in male and female offspring 125 . Post-weaning incorporation of fish oil into the diet prevented programmed dyslipidemia and liver steatosis in males in a high sucrose diet programming model 126 . In a model of uteroplacental insufficiency-induced IUGR, maternal administration of docosahexaenoic acid during pregnancy and lactation prevented programmed adiposity and alterations in PPARγ expression and increased circulating adiponectin concentrations in males but not females 127 …”
Section: Potential Intervention Strategies To Prevent Developmental Pmentioning
confidence: 97%
“…125 Post-weaning incorporation of fish oil into the diet prevented programmed dyslipidemia and liver steatosis in males in a high sucrose diet programming model. 126 In a model of uteroplacental insufficiency-induced IUGR, maternal administration of docosahexaenoic acid during pregnancy and lactation prevented programmed adiposity and alterations in PPARγ expression and increased circulating adiponectin concentrations in males but not females. 127 Omega-3 PUFA administration has been shown to be beneficial in a range of programming models, and effective during various exposure periods.…”
Section: Nutritional Interventionsmentioning
confidence: 99%
“…en este contexto, la presencia de chía desde el destete mejora a nivel hepático los índices de elongasas y desaturasas (estimados por la relación entre el contenido los ácidos grasos 18:0/16:0 y 18:1 n-9/ 18:0 respectivamente) así como su relación con el contenido hepático de tg (104). estos resultados están en concordancia con la habilidad de los PUFAs en suprimir la expresión del SReBP1c (112) y de la estearoil-coA desaturasa (SCd) (113) y en activar los genes involucrados en la oxidación de los ácidos graos (2, 114,115). el normal contenido de los tg hepáticos en las crías donde la chía estuvo presente desde el destete, se correlaciona directamente con la normalización de las actividades enzimáticas FAS, ACC, G-6-PdH y Me (síntesis "de novo" de ácidos grasos) y CPt-1 (relacionada a la oxidación mitocondrial de ácidos grasos).…”
Section: Efectos De La Semilla De Chia Dietaria Luego Del Desteteunclassified